2017
DOI: 10.1038/s41598-017-17772-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the permeability of Escherichia coli using MAC13243

Abstract: The outer membrane of gram-negative bacteria is a permeability barrier that prevents the efficient uptake of molecules with large scaffolds. As a consequence, a number of antibiotic classes are ineffective against gram-negative strains. Herein we carried out a high throughput screen for small molecules that make the outer membrane of Escherichia coli more permeable. We identified MAC13243, an inhibitor of the periplasmic chaperone LolA that traffics lipoproteins from the inner to the outer membrane. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 57 publications
4
95
1
Order By: Relevance
“…The authors of that study showed that this molecule makes cells more susceptible to bulky antibiotics, like vancomycin, that are normally excluded by the outer membrane. Given the prior connection of MAC13243 with LolA (26), it was concluded that the permeability defect induced by the compound was a result of its interference with the lipoprotein transport pathway (38). However, based on our analysis described above, we reasoned that the observed effect of MAC13243 was more likely to result from its breakdown product inhibiting the Rod system.…”
Section: Relationship Between Mic and Mecillinam Suppression Activitymentioning
confidence: 86%
See 1 more Smart Citation
“…The authors of that study showed that this molecule makes cells more susceptible to bulky antibiotics, like vancomycin, that are normally excluded by the outer membrane. Given the prior connection of MAC13243 with LolA (26), it was concluded that the permeability defect induced by the compound was a result of its interference with the lipoprotein transport pathway (38). However, based on our analysis described above, we reasoned that the observed effect of MAC13243 was more likely to result from its breakdown product inhibiting the Rod system.…”
Section: Relationship Between Mic and Mecillinam Suppression Activitymentioning
confidence: 86%
“…Rod system inactivation results in an outer membrane permeability defect. MAC13243 was also recently identified in a high-throughput screen for molecules that disrupt the outer membrane permeability barrier of E. coli (38). The authors of that study showed that this molecule makes cells more susceptible to bulky antibiotics, like vancomycin, that are normally excluded by the outer membrane.…”
Section: Relationship Between Mic and Mecillinam Suppression Activitymentioning
confidence: 99%
“…An independent screen illustrated that MAC13243 treatment caused increased cellular permeability in E. coli, which also occurs when LolA levels are depleted [131]. MAC13243 and A22 were suggested to act on LolA to permeabilize the OM.…”
Section: Inhibiting Lipoprotein Transportmentioning
confidence: 99%
“…To this extent, a high-throughput analysis revealed the small molecule MAC13243 as membrane permeabiliser to facilitate increased influx of large antibiotics in E. coli. This molecule was identified as an inhibitor of the LolA, a periplasmic chaperone that traffics lipoproteins from the inner to the OM [103].…”
Section: Om Permeabilisersmentioning
confidence: 99%